(untitled) (CIPEEX, 2022)
A CITY THAT HAS ADEQUATE ROADS FOR PEDESTRIANS TO MOVE AROUND AVOIDS ACCIDENTS, DAMAGES, AND COLLABORATES WITH THE URBAN MOBILITY OF VEHICLES. HOWEVER, NOT ALL NEIGHBORHOODS IN A MUNICIPALITY HAVE URBAN PAVING, SOME WITH PRECARIOUS ASPHALT AND OTHERS THAT DO NOT EVEN HAVE SIDEWALK. THEREFORE, THE PURPOSE OF THIS STUDY IS TO OBSERVE WHETHER THE BURITI AND PARASO RESIDENCIALS I AND II HAVE ADEQUATE URBAN INFRASTRUCTURE REGARDING THE PAVING OF PUBLIC ROADS. TO OBTAIN THE EXPECTED ANSWERS, THE FOLLOWING SPECIFIC OBJECTIVES WERE ELABORATED: A) TO ADDRESS THE DUTY OF THE MUNICIPAL PUBLIC POWER IN RELATION TO URBAN INFRASTRUCTURE; B) TO DISCUSS URBAN MOBILITY AND ACCESSIBILITY THROUGH THE POLICY OF PAVING PUBLIC ROADS; C) TO OBSERVE WHETHER THE CITY OF SENADOR CANEDO HAS PROPERLY PAVED PUBLIC ROADS FOR DRIVING VEHICLES. THEREFORE, THE FOLLOWING QUESTION WAS ESTABLISHED AS A GUIDING PROBLEM FOR THIS ANALYSIS: DOES THE MUNICIPALITY OF SENADOR CANEDO HAVE SAFE PUBLIC ROADS FOR VEHICLE LOCOMOTION? WHICH RIGHTS ARE VIOLATED BY THE LACK OF INVESTMENT IN URBAN MOBILITY INFRASTRUCTURE POLICIES? THE FOLLOWING METHODS WERE USED TO OBTAIN THE DATA REQUIRED TO CONDUCT THE RESEARCH: QUALITATIVE-QUANTITATIVE RESEARCH, FIELD AND EXPLANATORY RESEARCH. THE STUDY PRESENTED HERE IS CONSIDERED OF GREAT IMPORTANCE FOR THE SOCIETY OF THE TOWN OF SENADOR CANEDO, BECAUSE FROM THE RESULTS OBTAINED IT WILL BE POSSIBLE TO FOSTER DISCUSSION ABOUT THE APPLICABILITY OF THE PARTICIPATORY MUNICIPAL PUBLIC BUDGET, SINCE THROUGH PUBLICITY THE RESIDENTS WILL BE AWARE OF THE REALITY EXPERIENCED AND THUS BE ABLE TO CLAIM THEIR RIGHTS, AND EVEN REDUCE DAMAGES AND ACCIDENTS FOR THE POPULATION OF SENADOR CANEDO. THE PAVING OF PUBLIC ROADS IS A DUTY OF THE MUNICIPALITY THROUGH THE SECRETARIAT OF INFRASTRUCTURE AND WORKS (SEINFRA), ALSO PROVIDED FOR IN THE MUNICIPAL ORDINARY LAW NO. 2465 OF 2021, ACCORDING TO ITS ART. 33 CAPUT AND SUBSECTION I. THEREFORE, THE NEED FOR THE PROPOSED RESEARCH IS EVIDENT, SINCE THE RESULTS OBTAINED WERE SO WORRISOME THAT THEY DESERVE TO BE HIGHLIGHTED ON THIS THEME.&NBSP;